Versatile near-infrared fluorescent probe for in vivo detection of Aβ oligomers. Issue 13 (1st July 2020) - Zeng, Fantian; Yang, Jian; Li, Xiaofang; Peng, Kewen; Ran, Chongzhao; Xu, Yungen; Li, Yuyan
Graphical abstract: We developed a versatile NIR fluorescence probe PTO-41 for the detection of Aβ oligomers with high selectivity and excellent fluorescent properties. This probe could differentiate between 4 month-old APP/PS1 transgenic mice from wild-type mice during in vivo imaging. Highlights: The probe PTO-41 is a versatile NIR fluorescent probe for the detection of Aβ oligomers. The probe PTO-41 exhibits excellent functional properties both in vitro and in vivo. This probe PTO-41 has been successfully applied for the in vivo NIR fluorescent imaging of Aβ oligomers in 4 month-old APP/PS1 and differentiating from WT mice. Abstract: Amyloid-β oligomers (AβOs) enrichment in brain is highly related to Alzheimer's pathogenesis, but tracing them in the brain by imaging technique is still a great challenge due to their heterogeneity and metastability. Herein, a new near-infrared (NIR) fluorescent probe, namely, PTO-41, was designed and synthesized to specifically target AβOs. PTO-41 possesses excellent functional properties including optimal fluorescent properties (emission maxima at 680 nm upon interacting with AβOs), high affinity ( K d  = 349 nM), low cell toxicity, desirable lipophilicity (log P = 2.24), and fast wash out from the brain (brain2 min /brain60 min  = 5.0). Furthermore, PTO-41 exhibits a high sensitivity toward AβOs in vitro phantom imaging experiments. More importantly, PTO-41 shows great capacity to differentiate between 4-month-old APP/PS1 model mice from age-matched control mice using in vivo imaging. In summary, PTO-41 almost meets all the requirements as a versatile NIR fluorescent probe for the detection of AβOs both in vitro and in vivo .